The effectiveness of virtual journal clubs on evidence-based practices application - Beth Elenko (Revista Internacional de Educação e Saúde)
INTRODUCTION: This study examines the effectiveness of a virtual journal club (VJC) in enhancing students' understanding of evidence-based practice (EBP) and its application in occupational therapy (OT). Entry-level Master of Science (MS) and clinical Occupational Therapy Doctorate (OTD) students participated in a VJC over two semesters. The objective of the VJC is to foster group discussions in a non-threatening environment, preparing students for their future fieldwork and articulating evidence-based interventions in practice. OBJECTIVES: The purpose of this study was to examine the effectiveness of this VJC on the understanding and application of evidence-based practice. METHODS AND MATERIALS: Twenty-four entry-level MS and OTD students voluntarily took part in this study, completing pre- and post-tests using the OT-KACE survey. The OT-KACE is adapted from the Evidence Based Practice (EVP) Knowledge, Attitudes, Access, and Confidence Evaluation (KACE) developed by William Hendricson, School of Dentistry, The University of Texas Health Science Center at San Antonio. All students participated in the VJC as part of their research course sequence. RESULTS AND CONCLUSIONS: Significant improvements in understanding EBP were observed from pre to post OT-KACE assessments. EBP integration is a cornerstone of entry-level healthcare curricula. Engaging students in VJCs provides them with opportunities to explore and apply learned skills independently and collaboratively, aligning with contemporary learning preferences.